THE IMPACT OF CLOUD COMPUTING ON INFORMATION TECHNOLOGY IN THE BASRA OIL COMPANY AS A MODEL FOR THE STUDY (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to provide a theoretical framework explaining the impact of cloud computing and itsfields on information technology, as cloud computing has achieved a significant change in the economics and sustainability ofinformation technology, which is one of the most innovative technological models for the development and exploitation ofinfrastructure resources in the world, especially at the level of informatics. The shift from purchasing infrastructure andtechnology applications as an acquired product to a well-delivered service.The user no longer needs to search for large funding to purchase infrastructure equipment and related applications and a licenseto operate them. The cloud computing profession has not been isolated from keeping pace with these technologicaldevelopments, as those in charge and practitioners should understand these changes that require reorganizing the work of theunits they serve, as it should Programmers should be aware of the need to analyze and evaluate impacts and changes toinformation technology.